Why phenomenological theory cannot be used to analyze the dynamics of dark photorefractive solitons - Wichtowski, Marek (Photonics Letters of Poland, 2023)
The currently used theory of both bright and dark spatial photorefractive (PR) solitons is a phenomenological theory. In the work we consider the dynamics of dark beams using a microscopic model based on the PR transport equations. It is generally believed that such a theory is more accurate. It has been found that these two approaches can give completely different predictions regarding the formation time of dark beams. The discrepancies can reach up to two orders of magnitude. An approximate analytical solution was presented and a new time constant was introduced taking into account crystals from three classes of PR materials: ferroelectrics, sillenites and semiconductors. Full Text: PDF References A. Katti, R.A. Yadav, Optical Spatial Solitons in Photorefractive Materials (Singapore, Springer, 2021) CrossRef E. DelRe, M. Segev, Ch. 23 in Self-focusing: Past and Present, ed. by R.W. Boyd, S.G. Lukishova, Y.R. Shen (New York, Springer, 2009). CrossRef M. Wichtowski, "On conformity of solutions for one-dimensional photorefractive screening solitons with the Kukhtarev–Vinetskii model", Appl. Phys. B 120, 527 (2015). CrossRef M. Segev, B. Crosignani, P. Di Porto et al., in Photorefractive Spatial Solitons, (Kluwer Academic Publisher, New York, 2002). DirectLink K. Zhan, Ch. Hou, S. Pu, "Temporal behavior of spatial solitons in centrosymmetric photorefractive crystals", Opt. Laser Technol. 43, 1274 (2011). CrossRef J. Maufoy, N. Fressengeas, D.Wolfersberger, G. Kugel, "Simulation of the temporal behavior of soliton propagation in photorefractive media", Phys. Rev. E 59, 6116 (1999). CrossRef A. Katti, M.S. Pande, "Formation characteristics of dark solitons in photorefractive crystals having both linear and quadratic electro-optic effect simultaneously", Opt. Quantum Electron. 55, 1132 (2023). CrossRef